Improvement of mechanical behavior and microstructure of microcrystalline cellulose (MCC)-sisal fibre reinforced multiscale cementitious composites - Souza Filho, Aloysio Gomes de (2020)
This work reports the development of multiscale cementitious composites containing sisal fibres and microcrystalline cellulose (MCC), previously dispersed by ultrasonication and cetyltrimethylammonium bromide (CTAB), as the novel dispersing agent. The mechanical tests performed allowed to identify significant improvement in the mechanical properties, hydration degree, and microstructure.